Pengembangan Media Audio Menyimak Tematik Berbasis Fitrah Bagi Siswa Sekolah Dasar - Muhamad Fakhrur Saifudin; Hanum Hanifa Sukma (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aims to (1) Develop audio media with thematic listening skills based on the nature of elementary school students; (2) find out the feasibility of thematic listening media audio media based on the nature of elementary school students. The method used in this research is the research and development method. The model used is the ADDIE model consisting of 5 (five) steps, namely: (1) analysis (analyze), (2) design, (3) development, (4) implementation, and ( 5) evaluation. The results showed that based on the feasibility test based on the material, learning, and language expert validators stated that the media listened to thematic audio based on fitrah with the